2018
DOI: 10.1177/155892501801300205
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Surface Engineering and Deformation Response of Some Natural Polymer Fibrous Systems

Abstract: Surfaces of bamboo derived cellulosic fibrous systems have been modified by air-plasma treatment. Their deformational response was studied to establish the relationship between their three-dimensional profile and permanent deformation as a measure of their comfort properties since the fibrous system made of natural polymer comes into contact with the skin. The composite should have a permanent deformation close to zero, in order to be, in terms of dimensions, as stable as possible. By analyzing the area of 1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…This finding is endorsed by the removal of organic and inorganic surface contaminants by surface treatments. 45 The cationization of 6% displayed the lowest values of deformations (samples [13][14][15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is endorsed by the removal of organic and inorganic surface contaminants by surface treatments. 45 The cationization of 6% displayed the lowest values of deformations (samples [13][14][15].…”
Section: Resultsmentioning
confidence: 99%
“…Then, the sensor was shifted automatically by 1 mm to the right and the same procedure was repeated five times. We obtain the roughness values (R z ) and the average is calculated by equation (1) 45 Where:…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the coating process ensures the spreading of the surface following the coating doctor blade affecting the settling of particles on the surface. [ 6,42 ]…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the coating process ensures the spreading of the surface following the coating doctor blade affecting the settling of particles on the surface. [6,42] Moreover, by comparing the roughness values of two types of abrasives, it is observed that due to the large size of silica grains and their assembly at the same places as shown in Figure 6C, the roughness values are higher. It is found that the wear rates decrease with the decrease in grain size, which results in smoother surfaces.…”
Section: Roughness Testmentioning
confidence: 94%
See 1 more Smart Citation